Superdads: Migrant Fathers' Right to Family Life before the European Court of Human Rights. (October 2015) - de Hart, Betty
In discussions about multiculturalism, migration, Islam, and law, migrant and especially Muslim fathers have predominantly been discussed in terms of their overall power over women and children. The recurring question seems to be how much room they should be granted to have a polygamous marriage, keep their daughters out of school, and marry them off. This contribution argues that the sociolegal position of migrant fathers is much more complex and possibly more vulnerable than often perceived, as a consequence of the workings of family law and immigration law. Using (black) feminist critiques of family law, the question is to what extent migrant fathers' weaker legal position is being caused by ideologies about fatherhood in family law and immigration law that exclude them from being "good fathers." The argument is based on an analysis of European Court of Human Rights case law on affiliation, divorce, custody, visiting rights, and residence.